2015
DOI: 10.7235/hort.2015.15027
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Soil Moisture and Improvement of Indoor Air Quality by a Plant-Biofilter Integration System

Abstract: This study was performed to investigate the stability of soil moisture in controlling air ventilation rate within a horizontal biofilter, and to compare removal efficiency (RE) of indoor air pollutants including fine dust, volatile organic compounds (VOCs), and formaldehyde (HCHO), depending on whether dieffenbachias (Diffenbachia amoena) were planted in the biofilter. The relative humidity, air temperature, and soil moisture contents showed stable values, regardless of the presence of D. amoena, and the plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Lee et al ( 2015 ) tested the SPE of an active biofiltration system for the removal of xylene, ethylbenzene, toluene, benzene (all 1 ppmv), and formaldehyde (2 ppmv), finding removal efficiencies in the range of 71.3–75% for all VOCs except benzene (39.7%) and formaldehyde (44.9%). Unlike the findings of Wang ( 2011 ), the SPEs of the various VOCs tested by Lee et al ( 2015 ) were not correlated with their relative solubilities, which could be related to substrate differences between the systems. The relative abilities of different green wall substrates for VOC removal are still unclear and clearly require further research.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al ( 2015 ) tested the SPE of an active biofiltration system for the removal of xylene, ethylbenzene, toluene, benzene (all 1 ppmv), and formaldehyde (2 ppmv), finding removal efficiencies in the range of 71.3–75% for all VOCs except benzene (39.7%) and formaldehyde (44.9%). Unlike the findings of Wang ( 2011 ), the SPEs of the various VOCs tested by Lee et al ( 2015 ) were not correlated with their relative solubilities, which could be related to substrate differences between the systems. The relative abilities of different green wall substrates for VOC removal are still unclear and clearly require further research.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike potted-plant systems, where PM removal is limited to deposition on plant foliage, active systems pull air through the plant growth substrate, which can filter out a portion of the PM from the air stream (Irga et al, 2017b). Irga et al (2017b) and Lee et al (2015) revealed the potential for active green walls to effectively filter and reduce PM. While the use of highly adsorbent substrates has the potential to improve removal efficiency for VOCs, it is largely unknown how biofilter substrate design affects PM removal.…”
Section: Pm Removal By Functional Green Wallsmentioning
confidence: 99%
“…Furthermore, many studies have focused on assessing the short term or single pass pollutant removal efficiency (e.g. Darlington et al, 2001;Lee et al, 2015;Irga et al, 2017b;Pettit et al, 2017), thus there is a paucity of research relating to the CADR of these systems; although the CADR achieved by Wang and Zhang (2011) provides a promising insight into their potential. Similarly, the short-term experimental approach has largely left long-term effects on plant health unknown.…”
Section: Active Botanical Biofilter Experimental Designmentioning
confidence: 99%
“…The first attempt to test PM removal by an active green wall system was by Lee et al (2015), with their system removing 83 90% of PM -10 (particles with an aerodynamic diameter of <10 m), and 65 73% removal efficiency for PM μ -2.5 ( Figure 7), with efficacy depending on a 'humidifying' cycle, whereby water was atomised into the polluted airstream before entry into the biofilter substrate (Figure 8). Irga et al (2017) developed these trials further, using a commercial system (The Breathing Wall) developed by Australian company Junglefy Pty.…”
Section: The Performance Development Of Active Botanical Biofiltersmentioning
confidence: 99%
“…Active biofilter with humidifying system used byLee et al (2015). Reprinted from "Stabilization of soil moisture and improvement of indoor air quality by a plant-biofilter integration system, by C.H.Lee et al, 2015, Korean Journal of Horticultural Science and Technology, 33(5), pp.…”
mentioning
confidence: 99%